2014
DOI: 10.1016/s0325-7541(14)70095-1
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal variation in bacterioplankton composition and DNA damage in the microbial community from an Andean oligotrophic lake

Abstract: Laguna Azul is an oligotrophic lake situated at 4,560 m above sea level and subject to a high level of solar radiation. Bacterioplankton community composition (BCC) was analysed by denaturing gradient gel electrophoresis and the impact of solar ultraviolet radiation was assessed by measuring cyclobutane pyrimidine dimers (CPD). Furthermore, pure cultures of Acinetobacter johnsonii A2 and Rhodococcus sp. A5 were exposed simultaneously and CPD accumulation was studied. Gel analyses generated a total of 7 sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…The detrimental effect of UV on community production from waters exposed to high solar radiation for long periods of time are significant, but lower than that of communities previously unexposed (Hernández et al, 2006; Santos et al, 2012). This is supported by observed differences in the presence of phototolerant strains between communities with different solar exposure histories (Fernández-Zenoff et al, 2006; Zenoff et al, 2014; Albarracín et al, 2016). …”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…The detrimental effect of UV on community production from waters exposed to high solar radiation for long periods of time are significant, but lower than that of communities previously unexposed (Hernández et al, 2006; Santos et al, 2012). This is supported by observed differences in the presence of phototolerant strains between communities with different solar exposure histories (Fernández-Zenoff et al, 2006; Zenoff et al, 2014; Albarracín et al, 2016). …”
Section: Introductionmentioning
confidence: 63%
“…High levels of UV radiation are known to affect cell structure, function, and integrity (Häder et al, 2015). As a result, phototolerant or resistant microbial strains dominate in systems exposed to high solar radiation (Fernández-Zenoff et al, 2006; Flores et al, 2009; Paulino-Lima et al, 2013; Zenoff et al, 2014). In marine systems, bacterial secondary production (BSP) under solar radiation has been shown to depend on the solar exposure history (photobiological history) of the bacterioplankton community (Jeffrey et al, 1996a,b; Hernández et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Metagenomic approaches performed by Denaturing Gradient Gel Electrophoresis (DGGE), 16S rRNA gene clone libraries or 16s rDNA pyrotag sequencing indicated that prokaryotic communities from shallow water and sediment samples of HAAL are dominated by bacterial taxa of proteobacteria, bacteroidetes and firmicutes, whereas actinobacteria, cyanobacteria and spirochetes are less abundant (3,5,(7)(8)(9)11,12,14,(41)(42)(43)(45)(46)(47)69,70). Within Archaea, halophilic Euryarchaeota (Halobacteria), non-halophilic Euryarchaeota and mesophilic Crenarchaeota were described (11,24,43,69).…”
Section: Polyextremophiles: When One Extreme Is Not Enoughmentioning
confidence: 99%
“…Thus, HAAL provides natural laboratories for in situ exploring and monitoring of the interactions between the geophysical environment and the dynamics of microbiodiversity. Accordingly, HAAL-isolated strains display intrinsic high UV resistance (3)(4)(5)8,10,14,(16)(17)(18)(19) that render models for studying adaptive responses and mechanisms that underlie light sensing and UV resistance in environmental microbes. In fact, the availability of genomes of model polyextremophilic microbes (17,20) and several metagenomes of complex microbial communities in microbialites is providing a great opportunity to perform in-depth basic and applied research (4,6,19,(21)(22)(23)(24)(25)(26)(27)(28)(29).…”
Section: Introductionmentioning
confidence: 99%
“…Indigenous microorganisms originally isolated from irradiated environment are in general well adapted to high UV exposure . This is also the case for HAAL's strains that display intrinsically high UV resistance and are now considered novel models for studying adaptive responses and mechanisms of light sensing and UV‐triggered mechanisms .…”
Section: Introductionmentioning
confidence: 99%